Process control fundamentals : analysis, design, assessment, and diagnosis - Rengaswamy, Raghunathan; Srinivasan, Babji; Bhatt, Nirav Pravinbhai (Boca Raton : CRC Press, 2020)
"This comprehensive textbook covers key aspects including analysis, design, assessment and diagnosis of process control. It will help serve as ideal study material for senior undergraduate and graduate students in the field of chemical engineering for a course on process control"--
OCLC-licensed vendor bibliographic record.
Keywords: Chemical process control; TECHNOLOGY / Engineering / Chemical & Biochemical